Investigating the Interaction between Dichotic Deficits and Cognitive Abilities Using the Dichotic Digits difference Test (DDdT) Part 2 - Cameron, Sharon; Glyde, Helen; Dillon, Harvey; Whitfield, Jessica (Journal of the American Academy of Audiology, 2016)
Background: The Dichotic Digits difference Test (DDdT) was developed to investigate the relationship between dichotic processing and cognitive abilities and, through the use of differential test scores, to provide professionals with a clinical tool that could aid in differentiation of clients with genuine dichotic deficits from those where cognitive disorders affect test performance. The DDdT consists of four subtests: dichotic free recall (FR), dichotic directed left ear, dichotic directed right ear, and diotic. Scores are calculated for six conditions: FR left ear (LE), right ear (RE), and total, as well as the directed left ear, directed right ear, and diotic, and four difference measures: dichotic advantage, RE advantage FR, RE advantage directed, and attention advantage.Purpose: To investigate the role of cognitive abilities on DDdT test performance.Research Design: Correlational analysis between the various DDdT conditions and difference measures, as well as between dichotic, diotic, and cognitive factors (memory, intelligence, and attention).Study Sample: Fifty typically developing children (aged 7 yr 0 mo to 12 yr 1 mo, mean = 9 yr 2 mo) and ten children recruited from the Australian Hearing CAPD Service who were diagnosed with a memory or dichotic deficit (aged 7 yr 0 mo to 15 yr 0 mo, mean = 9 yr 5 mo) took part in the study.Data Collection and Analysis: The Pearson product moment correlations were used to determine the strength of relationships between DDdT conditions as well as relationships between scores on these conditions and performance on the various cognitive assessment tools, which included the number memory forward and reversed subtests of the Test of Auditory Processing Skills – Third Edition, IVA + Plus Continuous Performance Test, and the Test of Non-Verbal Intelligence-4 (TONI-4). A parent questionnaire (Fisher’s Auditory Checklist) and a participant questionnaire (Listening Inventory for Education) were also administered.Results: Diotic performance was significantly correlated with performance on all the DDdT dichotic FR conditions (r = 0.6–0.8; p < 0.00001). Further, significant correlations were found between the FR LE, total, and diotic conditions, and the cognitive measures of attention and memory, with r ranging from 0.4 to 0.5 (p < 0.01–0.001). Right-ear performance was not significantly correlated to any cognitive measure, except for FR RE and number memory forward (r = 0.35; p = 0.006). The DDdT dichotic advantage measure was investigated in a subset of clinical children and found to aid in differentiating true dichotic from spurious results.Conclusions: As found in the DDdT normative data study that precedes in the companion paper (DDdT Study Part 1; Cameron et al, 2016), the high correlation between dichotic and diotic performances by the clinical and typically developing participants suggests that factors other than dichotic performance play a substantial role in a child’s ability to perform a dichotic listening task. Indeed, 61% of the variance in FR total scores for the children in this study was accounted for by factors that do not involve the perception of dichotic stimuli. This view is supported by the correlations between measures of attention and memory and dichotic scores. This result has wide-spread implications in respect to interpretation of central auditory processing disorder test results and further investigation of the use of the DDdT in a clinical population is warranted.
Keywords: central auditory processing disorder; dichotic; diotic; directed; free recall; impulsivity; sustained attention